A Method for Selecting Ground Motions that Considers Target Response Spectrum Mean and Variance as Well as Correlation Structure. Issue 8 (16th November 2016) - Ha, Seong Jin; Han, Sang Whan
Abstract : This study proposes a method for selecting ground motions from a ground motion library with response spectra that match the target response spectrum mean, variance, and correlation structures. The proposed method is conceptually simple and straightforward. In this method, a desired number of ground motions are sequentially selected from first to last. The accuracy and consistency of the proposed method are verified through comparisons of the ground motions selected using the proposed method with those selected using conventional methods. This study shows that the seismic responses of the frames vary according to ground motion selection and correlation structures.